CHALLENGES OF EVALUATION OF THE INFLUENCE OF ENTREPRENEURSHIP EDUCATION - Sunčica Oberman Peterka; Tihana Koprivnjak; Petra Mezulić (Economic Review)
The need for entrepreneurial behaviour and activity in all aspects of life is becoming more pronounced, and education has a decisive role in the creation of an entrepreneurial society and entrepreneurial culture. The number of educational programmes in entrepreneurship at all levels of education is steadily increasing worldwide. It is often said that entrepreneurship education is one of the most important development and economic mechanisms. Organizational structure, content, methodology and pedagogy differ from programme to programme, but all of them are created because of similar motives: to stimulate economic development of the environment in which they operate. Entrepreneurship education has a positive influence on the development of entrepreneurial spirit of young people, their intentions towards starting their own business, their employability and, ultimately, their role in society and economy. Although the importance of entrepreneurship education is almost universally accepted, there are numerous problems in measuring the impact of such education. In the case of entrepreneurship education, the traditional tools for assessing the knowledge acquired are not applicable. The objective of the paper is to present the different approaches in evaluation of impact of entrepreneurship education and to introduce a tool for assessing the impact of entrepreneurship education, developed within the European project ASTEE1. The aim of the ASTEE project was to develop a joint European tool for measuring the effects of education for development of entrepreneurial competences at all educational levels (primary, secondary and tertiary education). The paper will also present the results of research conducted within the project in Croatia.